2013
DOI: 10.1159/000356527
|View full text |Cite
|
Sign up to set email alerts
|

The Brain of the Horse: Weight and Cephalization Quotients

Abstract: The horse is a common domestic animal whose anatomy has been studied since the XVI century. However, a modern neuroanatomy of this species does not exist and most of the data utilized in textbooks and reviews derive from single specimens or relatively old literature. Here, we report information on the brain of Equus caballus obtained by sampling 131 horses, including brain weight (as a whole and subdivided into its constituents), encephalization quotient (EQ), and cerebellar quotient (CQ), and comparisons with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
33
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 38 publications
3
33
2
Order By: Relevance
“…The alpaca is a species with considerably long gestation (340 days) and possesses a gyrencephalic brain (presenting sulci and gyri). These morphological and gestational characteristics are closer to other Cetartiodactyla, such as pig ( Sus scrofa ), bovine ( Bost taurus ), sheep ( Ovis aries ), giraffe ( Giraffa camelopardalis ; Ballarin et al, ; Graïc et al, ); Perissodactyla, as the horse (Cozzi et al, ); and apes. The specimens that we used in our experimental set were accompanied by notes referring to the age (in days) of the embryos and fetuses.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…The alpaca is a species with considerably long gestation (340 days) and possesses a gyrencephalic brain (presenting sulci and gyri). These morphological and gestational characteristics are closer to other Cetartiodactyla, such as pig ( Sus scrofa ), bovine ( Bost taurus ), sheep ( Ovis aries ), giraffe ( Giraffa camelopardalis ; Ballarin et al, ; Graïc et al, ); Perissodactyla, as the horse (Cozzi et al, ); and apes. The specimens that we used in our experimental set were accompanied by notes referring to the age (in days) of the embryos and fetuses.…”
Section: Discussionmentioning
confidence: 62%
“…This stratification reflects the process of differentiation and migration of the germinal neuroepithelium cells that will eventually form the cortical columns of the neocortex (Gilbert, ), here organized in five layers as typical of large herbivores (Cozzi et al, ; van Kann et al, ). However, here we note that adult Cetartiodactyla and Perissodactyla, contrarily to rodents and primates, are generally considered to be endowed with a five‐layered cortex, for further discussion see (Cozzi et al, , ).…”
Section: Discussionmentioning
confidence: 78%
“…The giraffe seems to have not only the biggest brain among terrestrial Cetartiodactyla in absolute mass, together with the hippopotamus, but also the largest EQ (Table ). It is notably lower than that of the odd‐hoofed horse, with 0.78 (Cozzi et al, ).…”
Section: Discussionmentioning
confidence: 92%
“…First of all we emphasize that our values originate from a direct calculation of brain and body weight derived from captive, but well housed, fed and groomed, mature specimens. Second, intraspecific variation may sometimes yield huge differences: In a recent study of our group (Cozzi et al, ), 7 out of 131 horses showed an EQ in the cat or primate range. An EQ of 0.76 for the giraffe is also more consistent with the Ruminantia clad (0.86, Boddy et al ; Ballarin et al ).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation